THE MODELING OF DIRECTION FINDING SYSTEM AND LOCATION DETERMINATION OF CLOSED RADIO EMISSION SOURCES - Vladimir Vasilievich Fedorenko; Aleksandr Ivanovich Sivakozov (Вестник Северо-Кавказского федерального университета)
The method of location determination modeling system of emission sources closed to direct range by the reflected rays in view account the errors of bearings and uncertainties values of the model parameters is considered.